A Volumetric MRI Analysis of Hypochondriac Patients - Atmaca, Murad; Sec, Semih; Yildirim, Hanefi; Kayali, Alperen; Korkmaz, Sevda (Kure Iletisim Grubu A S, 2010)
No volumetric brain magnetic resonance imaging (MRI) study has been performed in hypochondriac patients to date. In the present study, we aimed to volumetrically evaluate the orbito-frontal cortex (OFC), anterior cingulate, caudate nucleus, and thalamus. The volumes of the OFC, thalamus, caudate nucleus, and anterior cingulate cortex were measured in 16 treatment-naive hypochondriac patients and 16 healthy control subjects. Volumetric measurements were made with T1-weighted coronal MRI images, with 1.5-mm-thick slices, at 1.5T and were done blindly. Hypochondriac patients had significantly smaller mean left and right OFC, and greater left but not right thalamus volumes compared with healthy controls. There was no difference in regard to caudate and anterior cingulate volumes for either side between groups. The Hamilton Depression Rating Scale (HDRS) scores were not associated with any volumetric parameter studied. Age at onset showed a significant relationship to left OFC, and left thalamus volumes. Duration of illness also exhibited a significant association with left OFC, and left thalamus volumes. In conclusion, this morphometric MRI study showed that patients with hypochondriasis had smaller left and right OFC and significantly greater left thalamus volumes compared to healthy controls. Taken together, our findings suggest that abnormalities in the OFC and thalamus seem to play an important role in the pathophysiology of hypochondriasis.
Keywords: MRI; Volumetric; hypochondriasis; Anterior cingulate; OFC; Thalamus; Caudate